Stretched film, and metal laminate film and film capacitor which use the same

JP2025013494A5Active Publication Date: 2025-01-31OJI HLDG CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024193704
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-25
Filing Date
2024-11-05
Publication Date
2025-01-31
Estimated Expiration
2044-04-24

AI Technical Summary

Technical Problem

Conventional polypropylene films used in film capacitors face challenges in maintaining rigidity and electrical insulation at high temperatures exceeding 110°C, particularly in environments above 120°C, and are prone to breaking during processing due to the formation of pores during extension, which affects their physical properties and productivity.

Method used

A specific composition of extended film comprising 55% to 99% polypropylene resin and 1% to 45% polymer with an alicyclic structure in the side chain, extended in one direction, with a glass transition temperature between 100°C and 180°C, and a thickness of 10 μm or less, is used to enhance rigidity and electrical insulation, and a metal laminated film is applied for improved processing.

Benefits of technology

The solution effectively suppresses the decrease in rigidity and electrical insulation at high temperatures, ensuring excellent processability and maintaining electrical characteristics even in extreme conditions, with enhanced dielectric breakdown strength and reduced breakage during metal vapor deposition.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a stretched film which suppresses lowering of physical properties such as lowering of rigidity and lowering of electric insulation property, even under high temperature environment exceeding 110°C, and is also excellent in stretchability and post-processing process passing property of itself.SOLUTION: A stretched film has at least a layer A, wherein (1) the layer A contains, in 100 mass%, 55 mass% or more and 99 mass% or less of a polypropylene-based resin, and 1 mass% or more and 45 mass% or less of a polymer having an alicyclic structure at a side chain, and (2) the layer A is stretched in at least one direction.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a stretched film, a metal laminated film and a film capacitor using the same, and in particular to a stretched film having excellent heat resistance suitable for capacitor applications. [Background technology]

[0002] Stretched films mainly made of polypropylene are used for various industrial applications including packaging because they have moisture resistance, rigidity, heat resistance, etc. In recent years, as their applications expand, there has been a demand for higher performance, and in particular, there is a demand for suppression of loss of rigidity at high temperatures.

[0003] In addition, stretched films mainly made of polypropylene are used for film capacitor applications due to their excellent electrical properties. Film capacitors made of stretched films mainly made of polypropylene are used in electronic devices, electrical devices, etc., for example, as high-voltage capacitors, various switching power supplies, filter capacitors for converters, inverters, etc., smoothing capacitors, etc. Film capacitors are used, for example, in inverters and converters that control drive motors in automobiles such as electric automobiles and hybrid automobiles, which have seen an increase in demand in recent years.

[0004] Film capacitors, particularly film capacitors for automobiles, are increasingly being used in high-temperature environments. For example, in devices (inverters, converters, etc.) that control the drive motors of automobiles, the use of semiconductors with high heat resistance (such as silicon carbide semiconductors) has been increasing in recent years. Accordingly, capacitors used in these devices are also required to have high heat resistance, for example, 120°C or higher, preferably 130°C or higher. The upper limit of the operating temperature of conventional capacitors using polypropylene films is said to be about 110°C, and it is extremely difficult to stably maintain electrical insulation in high-temperature environments exceeding this limit.

[0005] As one of the resin films with high heat resistance, a film made of a resin composition containing a polyolefin mainly composed of polypropylene and a hydrogenated block copolymer has been disclosed as a film having excellent heat resistance and particularly excellent water vapor impermeability (Patent Document 1).

[0006] Furthermore, as one of the resin films having high heat resistance, a film using a polypropylene resin and a resin having an alicyclic structure in the main chain of the polymer obtained by polymerizing a cyclic olefin monomer has been disclosed (Patent Document 2). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2014-37532 A [Patent Document 2] International Publication No. 2022 / 270577 Summary of the Invention [Problem to be solved by the invention]

[0008] Resin films mainly composed of polypropylene tend to show a decrease in physical properties such as a decrease in rigidity and electrical insulation when the temperature of use is high. In general, a resin film mainly composed of polypropylene is stretched in at least one direction, preferably two directions, to form a stretched film, thereby improving the rigidity and electrical insulation, and maintaining the rigidity and electrical insulation even in a high temperature range where the use temperature exceeds 110° C. However, when the use temperature is high, such as 120° C. or higher, or even 130° C. or higher, it is difficult for even a stretched film to maintain its rigidity and electrical insulation.

[0009] The film described in Patent Document 1 has excellent water vapor impermeability due to the inclusion of a hydrogenated block copolymer, but since it is an unstretched film, its rigidity and electrical insulation are not high. In addition, when stretching a mixed resin, there are many cases where rigidity and electrical insulation are reduced due to the generation of pores in the layer during stretching. Therefore, special consideration is required to find stretching conditions that improve the physical properties while suppressing the generation of pores, but Patent Document 1 does not disclose any knowledge regarding the stretching conditions.

[0010] In addition, Patent Document 2 discloses a stretched film made of a mixed resin that has excellent electrical properties at high temperatures, but the mixed cyclic olefin resin has an alicyclic structure in the polymer main chain, making the resin rigid. Therefore, there is a problem that the film is prone to breakage in post-processing steps (for example, metal deposition steps in capacitor film applications) due to the generation of pores in the layers during stretching, which means that productivity is poor.

[0011] In particular, for film capacitor applications, a thin film is required, for example, a thickness of 10 μm or less, preferably 5 μm or less, but in this thickness range, the film becomes more susceptible to breakage, and there is a production problem in that the film becomes even more susceptible to breakage when the film formation speed and deposition speed are increased in order to reduce costs.

[0012] Therefore, an object of the present invention is to provide a stretched film which is inhibited from decreasing in physical properties such as rigidity and electrical insulation even in a high-temperature environment exceeding 110°C (particularly in a high-temperature environment of 120°C or higher), and which is excellent in its own stretchability and passability through post-processing steps. [Means for solving the problem]

[0013] As a result of intensive research by the inventors to solve the above problems, they found that the above problems can be solved by a stretched film having at least Layer A, which has a specific composition and is stretched in at least one direction. Based on this finding, the inventors further researched and completed the present invention.

[0014] That is, the present invention relates to the following stretched film, a metal laminated film and a film capacitor using the same. 1. A stretched film having at least layer A, (1) The layer A contains, in 100% by mass, 55% by mass or more and 99% by mass or less of a polypropylene resin and 1% by mass or more and 45% by mass or less of a polymer having an alicyclic structure in a side chain, (2) The layer A is stretched in at least one direction. A stretched film characterized by: 2. The stretched film according to item 1, wherein the A layer contains, based on 100% by mass, 55% by mass or more and 97% by mass or less of a polypropylene resin and 3% by mass or more and 45% by mass or less of a polymer having an alicyclic structure in a side chain. 3. The stretched film according to item 1 or 2, wherein the polymer has a glass transition temperature of 100° C. or higher and 180° C. or lower. 4. The stretched film according to any one of items 1 to 3, wherein the alicyclic structure has a cyclohexane structure. 5. The stretched film according to any one of items 1 to 4, wherein the stretched film has a thickness of 10 μm or less and a total light transmittance of 80% or more. 6. A metal laminated film comprising the stretched film according to any one of items 1 to 5 above and a metal layer laminated on one or both sides of the film. 7. A film capacitor comprising the stretched film according to any one of items 1 to 5 above. 8. A film capacitor comprising the metal laminated film according to item 6 above. Effect of the Invention

[0015] According to the present invention, it is possible to provide a stretched film which is suppressed from decreasing in physical properties such as rigidity and electrical insulation even in a high-temperature environment exceeding 110°C, and which has excellent stretchability and passability through post-processing steps. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] In this specification, the expressions "contain" and "include" include the concepts of "contain", "include", "consist essentially of" and "consist only of". In this specification, when an upper limit and a lower limit are described for a preferred range, the combination thereof can be arbitrary. In addition, in this specification, a numerical range indicated by "A to B" includes the numerical values ​​at the ends, and means "A or more and B or less", unless otherwise specified.

[0017] 1. Stretched Film In one aspect, the present invention provides a stretched film having at least layer A, (1) The layer A contains, in 100% by mass, 55% by mass or more and 99% by mass or less of a polypropylene resin and 1% by mass or more and 45% by mass or less of a polymer having an alicyclic structure in a side chain, (2) The layer A is stretched in at least one direction. The present invention relates to a stretched film characterized by the above-mentioned (hereinafter, also referred to as "the stretched film of the present invention"). This will be described below.

[0018] 1-1. Polypropylene Resin Layer A of the stretched film of the present invention contains 55% by mass or more and 99% by mass or less of a polypropylene-based resin, with the mass of Layer A being 100% by mass.

[0019] Examples of the polypropylene-based resin include propylene homopolymers such as isotactic polypropylene and syndiotactic polypropylene; copolymers of propylene and other olefins (e.g., ethylene, 1-butene, etc.) (the copolymer may be a random copolymer or a block copolymer having at least two polymer blocks); long-chain branched polypropylene; and polypropylene-based resins produced from plant-derived raw materials.

[0020] Here, when the polypropylene-based resin is a copolymer of propylene and another olefin, the content of propylene in the copolymer is 50% by mass or more, preferably 80% by mass or more, and more preferably 90% by mass or more, based on 100% by mass of the polypropylene-based resin. Note that the polypropylene-based resin does not include a polypropylene-based resin having an alicyclic structure in a side chain.

[0021] The polypropylene resin contained in layer A may be one type or two or more types.

[0022] The content of the polypropylene resin contained in the A layer may be 55% by mass or more and 99% by mass or less, preferably 55% by mass or more and 97% by mass or less, more preferably 60% by mass or more and 90% by mass or less, and even more preferably 65% ​​by mass or more and 85% by mass or less. In this case, the rigidity, electrical insulation, and stretchability of the stretched film of the present invention are improved. Note that, in the case where the stretched film of the present invention is a multilayer film having other layers (such as a skin layer described later) in addition to the A layer, the effect of improving the stretchability includes the case where the entire multilayer film is stretched (the same applies below).

[0023] The melt mass flow rate (MFR) of the polypropylene resin contained in the layer A is preferably 0.5 g / 10 min to 6 g / 10 min, more preferably 1 g / 10 min to 5 g / 10 min, and even more preferably 1.5 g / 10 min to 4 g / 10 min, as measured at 230° C. and 2.16 kg weight. In this case, appropriate resin fluidity is obtained during stretching of the film, and stretchability is improved.

[0024] The melting point of the polypropylene resin contained in the layer A is preferably 155°C or higher. In this case, electrical insulation and stretchability at high temperatures are improved. The melting point is more preferably 160°C or higher and 180°C or lower, and even more preferably 163°C or higher and 170°C or lower.

[0025] The polypropylene resin contained in Layer A preferably has a mesopentad fraction of 95 mol% or more and 99.9 mol% or less. When the mesopentad fraction is 95 mol% or more, the rigidity and electrical insulation of the stretched film of the present invention are likely to be improved, and when the mesopentad fraction is 99.9 mol% or less, the stretchability is likely to be improved. The mesopentad fraction of the polypropylene resin is more preferably 96 mol% or more and 99.5 mol% or less, further preferably 97 mol% or more and 99.2 mol% or less, and particularly preferably 98 mol% or more and 99 mol% or less.

[0026] The heptane insoluble content (HI) of the polypropylene resin contained in Layer A is preferably 94% by mass or more and 99.9% by mass or less. When it is 94% by mass or more, the rigidity and electrical insulation of the stretched film are likely to be improved, and when it is 99.9% by mass or less, the stretchability is likely to be improved. The heptane insoluble content of the polypropylene resin is more preferably 96% by mass or more and 99.5% by mass or less, further preferably 97% by mass or more and 99.2% by mass or less, and particularly preferably 98% by mass or more and 99% by mass or less.

[0027] The number average molecular weight (Mn) of the polypropylene resin contained in Layer A is preferably from 30,000 to 70,000, and more preferably from 35,000 to 65,000. When Layer A contains a polypropylene resin with such a number average molecular weight (Mn), the rigidity, electrical insulation, and stretchability of the stretched film of the present invention are easily improved.

[0028] The weight average molecular weight (Mw) of the polypropylene resin contained in Layer A is preferably from 250,000 to 500,000, and more preferably from 300,000 to 450,000. When Layer A contains a polypropylene resin having such a weight average molecular weight (Mw), the rigidity, electrical insulation, and stretchability of the stretched film of the present invention are likely to be improved.

[0029] The polypropylene resin contained in Layer A has a molecular weight distribution (Mw / Mn) calculated as the ratio of weight average molecular weight (Mw) to number average molecular weight (Mn) of preferably 3 to 12, more preferably 5 to 10, and even more preferably 6 to 9.5. When Layer A contains a polypropylene resin with such a molecular weight distribution (Mw / Mn), the rigidity, electrical insulation, and stretchability of the stretched film of the present invention are likely to be improved.

[0030] The z-average molecular weight (Mz) of the polypropylene resin contained in Layer A is preferably from 700,000 to 3,000,000, and more preferably from 1,000,000 to 2,500,000. When Layer A contains a polypropylene resin having such a z-average molecular weight (Mz), the rigidity, electrical insulation, and stretchability of the stretched film of the present invention are likely to be improved.

[0031] The polypropylene resin contained in Layer A has a molecular weight distribution (Mz / Mw) calculated as the ratio of the z-average molecular weight (Mz) to the weight-average molecular weight (Mw) of preferably 2 to 7, more preferably 2.5 to 6, and even more preferably 3 to 5. When Layer A contains a polypropylene resin having such a molecular weight distribution (Mz / Mw), the rigidity, electrical insulation, and stretchability of the stretched film of the present invention are likely to be improved.

[0032] The polypropylene resin can be produced by a conventional method. Examples of the polymerization method include gas phase polymerization, bulk polymerization, and slurry polymerization. The polymerization may be a single-stage polymerization using one polymerization reactor, or a multi-stage polymerization using two or more polymerization reactors. The polymerization may be carried out by adding hydrogen or a comonomer as a molecular weight modifier to the reactor. As the polymerization catalyst, a conventional Ziegler-Natta catalyst or a metallocene catalyst can be used, and the polymerization catalyst may contain a cocatalyst component or a donor. The mesopentad fraction, melt mass flow rate, molecular weight, and molecular weight distribution of the polypropylene resin can be controlled by appropriately adjusting the polymerization catalyst and other polymerization conditions.

[0033] 1-2. Polymers with alicyclic structures in the side chains Layer A of the stretched film of the present invention contains 1% by mass to 45% by mass of a polymer having an alicyclic structure in a side chain, with the mass of Layer A being 100%. The polymer having an alicyclic structure in a side chain contained in Layer A may be one type or two or more types.

[0034] The content of the polymer having an alicyclic structure in the side chain contained in Layer A may be 1% by mass to 45% by mass, preferably 3% by mass to 45% by mass, more preferably 10% by mass to 40% by mass, and even more preferably 15% by mass to 35% by mass, which improves the rigidity, electrical insulation, and stretchability of the stretched film of the present invention.

[0035] Here, the alicyclic structure includes one or more saturated and / or unsaturated carbon ring structures having no aromaticity. The number of carbon ring structures may be two or more. The carbon ring structure may have a branched aliphatic hydrocarbon structure. The carbon ring structure is bonded directly or via a hydrocarbon chain to the hydrocarbon chain of the polymer main chain.

[0036] Examples of the carbon ring structure include monocyclic structures such as cycloalkane structures such as cyclopropane, cyclobutane, cyclopentane, cyclohexane, cycloheptane, cyclooctane, cyclononane, cyclodecane, cycloundecane, and cyclododecane, and cycloalkene structures such as cyclopropene, cyclobutene, cyclopropene, cyclohexene, cycloheptene, and cyclooctene. Examples of bicyclic structures include bicyclic alkane structures such as bicycloundecane, and bicyclic alkene structures such as norbornene and norbornadiene, which can be suitably used. Among these, from the viewpoint of stretchability, it is preferable to have a carbon ring structure having 4 to 8 carbon atoms, more preferably a monocyclic carbon ring structure having 4 to 8 carbon atoms, even more preferably a carbon ring structure of a monocyclic cycloalkane structure having 4 to 8 carbon atoms, and particularly preferably a cyclohexane structure.

[0037] The polymer main chain is mainly composed of aliphatic hydrocarbons. The polymer main chain may contain cyclic hydrocarbon structures and / or aromatic hydrocarbon structures as structural units, but it is preferable that they are not contained. The aliphatic hydrocarbons of the polymer main chain may have branches of aliphatic hydrocarbon structures and / or aromatic hydrocarbon structures.

[0038] The polymer having an alicyclic structure in the side chain may be a homopolymer having a structure having an alicyclic structure in the side chain as a structural unit. For example, it may be polyvinylcycloolefin obtained by homopolymerizing vinylcycloolefin. Examples of polyvinylcycloolefin include polyvinylcyclopropane, polyvinylcyclobutane, polyvinylcyclopentane, polyvinylcyclohexane, polyvinylcycloheptane, polyvinylcyclooctane, polyvinylcyclononane, polyvinylcyclodecane, polyvinylcycloundecane, and polyvinylcyclododecane. In the case of homopolymer, rigidity and electrical insulation in a high temperature environment are easily increased, which is preferable. Among them, polyvinylcyclopentane, polyvinylcyclohexane, and polyvinylcycloheptane are preferable, and polyvinylcyclohexane is most preferable.

[0039] (Method of manufacturing polymer having alicyclic structure in the side chain) The method for producing the polymer having an alicyclic structure in a side chain is not particularly limited, and the polymer can be produced using a known method such as a radical polymerization method, an ionic polymerization method (anionic polymerization method, coordination anionic polymerization method, etc.), for example, a polymerization method such as bulk polymerization, solution polymerization, or suspension polymerization.

[0040] Specifically, the polymer having an alicyclic structure in a side chain according to the present invention can be produced by carrying out a polymerization reaction using a known initiator such as an alkyllithium compound or a dilithium compound, and a monomer having an alicyclic structure (e.g., vinylcycloolefin, etc.) is sequentially polymerized; or a monomer having an alicyclic structure is sequentially polymerized, and then a coupling agent is added to carry out coupling.

[0041] A polymer having an alicyclic structure in a side chain can be produced by polymerizing a monomer having an aromatic ring structure (e.g., styrene) by a known method, followed by a hydrogenation reaction. The hydrogenation reaction can be carried out, for example, by the method described in the method for producing a hydrogenated block copolymer described later.

[0042] When produced by hydrogenation reaction, the hydrogenation rate to the aromatic ring structure is preferably 50 mol% or more, more preferably 80 mol% or more, even more preferably 85 mol% or more, particularly preferably 90 mol% or more, and even more particularly preferably 95 mol% or more. The hydrogenation rate may be 100 mol%. By setting the hydrogenation rate in the above range, it is preferable because stretchability tends to be improved.

[0043] The polymer having an alicyclic structure in the side chain may be a copolymer having a structural unit having an alicyclic structure in the side chain and one or more other structural units. The copolymer may be a random copolymer or a block copolymer having at least two polymer blocks. From the viewpoint of stretchability, a copolymer is preferred, and a block copolymer is more preferred.

[0044] Examples of other structural units include ethylene, propylene, butene, pentene, hexene, heptene, octene, etc., and may or may not have a side chain. In addition, both structural units having a side chain and structural units not having a side chain may be included. Examples of structural units having a side chain include, for example, propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, etc. as structural units. The other structural units may be unsaturated hydrocarbons, but from the viewpoint of electrical insulation, saturated hydrocarbons are preferred.

[0045] Here, when the polymer having an alicyclic structure in a side chain (hereinafter also referred to as "the polymer") contains propylene as another structural unit, the propylene content in the polymer is less than 50 mass%, preferably 20 mass% or less, and more preferably 10 mass% or less, based on the mass of the polymer being 100 mass%.

[0046] A polymer having an alicyclic structure in a side chain can be obtained, for example, by polymerizing a monomer having each structural unit by a known method. It can also be obtained by hydrogenating a polymer having an aromatic ring structure in a side chain. Hydrogenating a polymer having an aromatic ring structure in a side chain is preferable because it is easy to industrially obtain a polymer having an alicyclic structure in a side chain at low cost.

[0047] When a polymer having an aromatic ring structure in a side chain is hydrogenated, the polymer having an aromatic ring structure in a side chain may be a homopolymer or a copolymer. In the case of a copolymer, a block copolymer having at least a vinyl aromatic polymer block and a conjugated diene polymer block is preferable. By hydrogenating this, a hydrogenated block copolymer having at least a hydrogenated vinyl aromatic polymer block and a hydrogenated conjugated diene polymer block is obtained.

[0048] Hereinafter, a hydrogenated block copolymer having at least a hydrogenated vinyl aromatic polymer block and a hydrogenated conjugated diene polymer block will be described as one of the preferred embodiments.

[0049] (Hydrogenated vinyl aromatic polymer block) The hydrogenated vinyl aromatic polymer block contains structural units derived from vinyl aromatic compounds and hydrogenated therefrom. The hydrogenated vinyl aromatic polymer block contains structural units derived from vinyl aromatic compounds in an amount of 50% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably 100% by mass. By making the structural units derived from vinyl aromatic compounds 50% by mass or more, the rigidity and electrical insulation properties in a high-temperature environment are easily improved.

[0050] Examples of vinyl aromatic compounds include styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-propylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene, vinyltoluene, 1-vinylnaphthalene, 2-vinylnaphthalene, etc. The vinyl aromatic compound is preferably selected from styrene and α-methylstyrene, more preferably styrene.

[0051] The hydrogenated vinyl aromatic polymer block may be composed of only one type of the above vinyl aromatic compound, or may be composed of two or more types.

[0052] The hydrogenated vinyl aromatic polymer block may contain other structural units in addition to the structural units derived from the vinyl aromatic compound, such as structural units derived from isoprene, butadiene, 2,3-dimethyl-butadiene, 1,3-pentadiene, 1,3-hexadiene, etc.

[0053] The content of the hydrogenated vinyl aromatic polymer block is preferably 50% by mass or more and less than 100% by mass, based on the total of the hydrogenated vinyl aromatic polymer block and the hydrogenated conjugated diene polymer block (100% by mass). By making it 50% by mass or more, the rigidity and electrical insulation at high temperatures are likely to be improved. It is more preferably 60% by mass or more, even more preferably 70% by mass or more, and particularly preferably 80% by mass or more.

[0054] (Hydrogenated Conjugated Diene Polymer Block) The hydrogenated conjugated diene polymer block contains structural units derived from a conjugated diene and hydrogenated thereof. The hydrogenated conjugated diene polymer block contains 50% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably 100% by mass of structural units derived from a conjugated diene.

[0055] Conjugated dienes include, for example, butadiene, 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-butadiene, 1,3-pentadiene, 1,3-hexadiene, etc. The conjugated diene is preferably selected from butadiene and isoprene, more preferably butadiene.

[0056] The hydrogenated conjugated diene polymer block may contain a structural unit derived from a conjugated diene having no side chain. Examples of the conjugated diene having no side chain include butadiene, 1,3-pentadiene, and 1,3-hexadiene. The conjugated diene having no side chain is preferably butadiene.

[0057] In the hydrogenated conjugated diene polymer block, the bond form of the conjugated diene, i.e., the microstructure, is not particularly limited. For example, in the case of butadiene, the bond form can be 1,2-bond or 1,4-bond. In the case of isoprene, the bond form can be 1,2-bond, 3,4-bond or 1,4-bond. Only one of these bond forms may be present, or two or more of them may be present. When two or more bond forms are present, the ratio of the bond forms is not particularly limited.

[0058] The hydrogenated conjugated diene polymer block may contain other structural units than those derived from conjugated dienes, such as structural units derived from styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-propylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene, vinyltoluene, 1-vinylnaphthalene, and 2-vinylnaphthalene.

[0059] The content of the hydrogenated conjugated diene polymer block is preferably more than 0% by mass (e.g., 1% by mass or more) and 50% by mass or less, based on 100% by mass of the total of the hydrogenated vinyl aromatic polymer block and the hydrogenated conjugated diene polymer block. By making it 50% by mass or less, it is preferable because the rigidity and electrical insulation at high temperatures tend to be high. It is more preferably 40% by mass or less, even more preferably 30% by mass or less, and particularly preferably 20% by mass or less.

[0060] (Hydrogenation rate) In the hydrogenated vinyl aromatic polymer block according to the present embodiment, the hydrogenation rate of the aromatic ring of the hydrogenated vinyl aromatic polymer block is preferably 50 mol% or more, more preferably 80 mol% or more, even more preferably 85 mol% or more, particularly preferably 90 mol% or more, and even more particularly preferably 95 mol% or more. The hydrogenation rate may be 100 mol%. The hydrogenation rate of the carbon-carbon double bond derived from the conjugated diene of the hydrogenated conjugated diene polymer block is preferably 90 mol% or more, more preferably 95 mol% or more. The hydrogenation rate may be 100 mol%.

[0061] By setting the hydrogenation rate of the aromatic ring of the hydrogenated vinyl aromatic polymer block and / or the hydrogenation rate of the carbon-carbon double bond derived from the conjugated diene of the hydrogenated conjugated diene polymer block within the above-mentioned range, stretchability tends to be improved, which is preferable.

[0062] (Bonding Mode of Hydrogenated Block Copolymer) The bonding mode of the polymer blocks in the hydrogenated block copolymer may be any one of linear, branched and radial, and may be a combination of these.

[0063] For example, when the hydrogenated vinyl aromatic polymer block is represented by "X" and the hydrogenated conjugated diene polymer block is represented by "Y", examples of the bonding pattern include a diblock copolymer (XY), a triblock copolymer (XYX), a tetrablock copolymer (XYXY), a pentablock copolymer (XYXYX or YXYXY), etc. From the viewpoint of ease of production, the bonding pattern is preferably a diblock copolymer, a triblock copolymer, or a tetrablock copolymer.

[0064] Specific examples of hydrogenated block copolymers include hydrogenated block copolymers obtained by hydrogenating styrene-isoprene diblock copolymer (SI), styrene-butadiene diblock copolymer (SB), styrene-isoprene-styrene triblock copolymer (SIS), styrene-butadiene / isoprene-styrene triblock copolymer (SB / IS), and styrene-butadiene-styrene triblock copolymer (SBS), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-ethylene-propylene-styrene copolymer (SEPS), styrene-ethylene-ethylene-propylene-styrene copolymer (SEEPS), styrene-butylene-butadiene-styrene copolymer (SBBS), etc. Among these, hydrogenated block copolymers obtained by hydrogenating styrene-butadiene diblock copolymer (SB) are particularly preferred.

[0065] (Method of producing hydrogenated block copolymer) The method for producing the hydrogenated block copolymer is not particularly limited, and any known method such as anionic polymerization can be used.

[0066] Specifically, the hydrogenated block copolymer according to the present invention can be produced by carrying out a polymerization reaction using, for example, a method of sequentially polymerizing a vinyl aromatic compound and a conjugated diene using an alkyllithium compound as an initiator; a method of sequentially polymerizing a vinyl aromatic compound and a conjugated diene using an alkyllithium compound as an initiator and then coupling by adding a coupling agent; or a method of sequentially polymerizing a conjugated diene and then a vinyl aromatic compound using a dilithium compound as an initiator, followed by carrying out a hydrogenation reaction.

[0067] Examples of the alkyllithium compound include methyllithium, ethyllithium, n-butyllithium, sec-butyllithium, tert-butyllithium, and pentyllithium.

[0068] Examples of the coupling agent include divinylbenzene; polyfunctional epoxy compounds such as epoxidized 1,2-polybutadiene, epoxidized soybean oil, and 1,3-bis(N,N-glycidylaminomethyl)cyclohexane; halogen compounds such as dimethyldichlorosilane, dimethyldibromosilane, trichlorosilane, methyltrichlorosilane, tetrachlorosilane, and tetrachlorotin; ester compounds such as methyl benzoate, ethyl benzoate, phenyl benzoate, diethyl oxalate, diethyl malonate, diethyl adipate, dioctyl adipate, dimethyl phthalate, diethyl phthalate, dimethyl isophthalate, and dimethyl terephthalate; carbonate compounds such as dimethyl carbonate, diethyl carbonate, and diphenyl carbonate; and alkoxysilane compounds such as dimethyldimethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, tetramethoxysilane, tetraethoxysilane, bis(trimethoxysilyl)hexane, and bis(triethoxysilyl)ethane.

[0069] The dilithium compound includes naphthalene dilithium, dilithiohexylbenzene, and the like.

[0070] The polymerization reaction is preferably carried out in the presence of a solvent. The solvent is not particularly limited as long as it is inactive to the initiator and does not adversely affect the reaction, and examples thereof include saturated aliphatic hydrocarbons such as hexane, cyclohexane, heptane, octane, and decane; and aromatic hydrocarbons such as toluene, benzene, and xylene. The temperature of the polymerization reaction is preferably 0 to 100°C, more preferably 30 to 90°C, further preferably 40 to 80°C, and particularly preferably 50 to 80°C, from the viewpoint of controlling the microstructure. The time of the polymerization reaction is preferably 0.5 to 50 hours, from the viewpoint of controlling the microstructure.

[0071] In addition, a Lewis base may be used as a cocatalyst during the polymerization reaction. Examples of Lewis bases include ethers such as dimethyl ether, diethyl ether, and tetrahydrofuran; glycol ethers such as ethylene glycol dimethyl ether and diethylene glycol dimethyl ether; and amines such as triethylamine, N,N,N',N'-tetramethylethylenediamine, and N-methylmorpholine. These Lewis bases may be used alone or in combination of two or more.

[0072] The hydrogenation reaction may be carried out immediately after the polymerization reaction, or may be carried out after isolating the block copolymer after the polymerization reaction.

[0073] When the block copolymer is temporarily isolated after the polymerization reaction, the block copolymer can be isolated by pouring the polymerization reaction liquid obtained after the polymerization reaction into a poor solvent for the block copolymer, such as methanol, to solidify the block copolymer, or by pouring the polymerization reaction liquid together with steam into hot water to remove the solvent by azeotropy (steam stripping), and then drying the block copolymer.

[0074] The hydrogenation reaction of the block copolymer can be carried out, for example, in the presence of a hydrogenation catalyst under conditions of a reaction temperature of 20 to 200° C. and a hydrogen pressure of 0.1 to 20 MPa for 0.1 to 100 hours.

[0075] Examples of the hydrogenation catalyst include Raney nickel; heterogeneous catalysts in which a metal such as platinum (Pt), palladium (Pd), ruthenium (Ru), rhodium (Rh), or nickel (Ni) is supported on a carrier such as carbon, alumina, or diatomaceous earth; Ziegler-based catalysts consisting of a combination of a transition metal compound (nickel octylate, nickel naphthenate, nickel acetylacetonate, cobalt octylate, cobalt naphthenate, cobalt acetylacetonate, or the like) and an organoaluminum compound such as triethylaluminum or triisobutylaluminum, or an organolithium compound, or the like; and metallocene-based catalysts consisting of a combination of a bis(cyclopentadienyl) compound of a transition metal such as titanium, zirconium, or hafnium, and an organometallic compound such as lithium, sodium, potassium, aluminum, zinc, or magnesium, or the like.

[0076] When the hydrogenation reaction is carried out successively to the polymerization reaction, the hydrogenated block copolymer can be isolated by pouring the hydrogenation reaction liquid into a poor solvent for the hydrogenated block copolymer, such as methanol, to coagulate it, or by pouring the hydrogenation reaction liquid together with steam into hot water to remove the solvent by azeotropy (steam stripping), followed by drying.

[0077] The glass transition temperature (Tg) of the polymer having an alicyclic structure in a side chain contained in Layer A of the present invention is preferably 100° C. or more and 180° C. or less. By setting the glass transition temperature to 100° C. or more, the rigidity and electrical insulation at high temperatures are likely to be increased, and by setting the glass transition temperature to 180° C. or less, the stretchability can be improved. The glass transition temperature is more preferably 120° C. or more and 165° C. or less, more preferably 130° C. or more and 160° C. or less, and particularly preferably 140° C. or more and 155° C. or less.

[0078] The Vicat softening point (1 kg, 50° C. / hr) of the polymer having an alicyclic structure in the side chain contained in the A layer is preferably 100° C. or higher and 170° C. or lower. By setting the Vicat softening point to 100° C. or higher, the rigidity and electrical insulation at high temperatures are likely to be increased, and by setting it to 170° C. or lower, the stretchability can be improved. The Vicat softening point is more preferably 120° C. or higher and 165° C. or lower, more preferably 130° C. or higher and 160° C. or lower, and particularly preferably 140° C. or higher and 155° C. or lower.

[0079] The glass transition temperature (Tg) and Vicat softening point of the polymer having an alicyclic structure in its side chain contained in Layer A can be adjusted by the type of structural unit having the above-mentioned alicyclic structure in its side chain and the types and ratios of one or more other structural units.

[0080] The weight average molecular weight (Mw) of the polymer having an alicyclic structure in a side chain contained in Layer A is not particularly limited, but is preferably from 50,000 to 400,000. When Layer A contains a polymer having an alicyclic structure with such a weight average molecular weight (Mw), the rigidity, electrical insulation, and stretchability of the stretched film of the present invention are likely to be improved.

[0081] The melt mass flow rate (MFR) of the polymer having an alicyclic structure in the side chain contained in the layer A is preferably 1 g / 10 min to 40 g / 10 min, more preferably 2 g / 10 min to 20 g / 10 min, and even more preferably 3 g / 10 min to 15 g / 10 min, when measured at 260° C. and 2.16 kg weight. In this case, appropriate resin fluidity is obtained during stretching of the film, and stretchability is easily improved.

[0082] The polymer having an alicyclic structure in the side chain contained in layer A may be produced by the above-mentioned method, or a commercially available product such as ViviOn (registered trademark) (manufactured by USI Corporation) may be used.

[0083] 1-3. A layer The present invention has Layer A containing 55% by mass to 99% by mass of a polypropylene resin and 1% by mass to 45% by mass of a polymer having an alicyclic structure in a side chain, where the mass of Layer A is 100% by mass. The Layer A is stretched in at least one direction.

[0084] Layer A may further contain other resins for the purposes of adjusting the low-temperature impact resistance of the film, adjusting the surface roughness, and adjusting various physical properties such as rigidity, strength, and elongation, as well as adjusting the mixability and stretchability of the polypropylene resin and the polymer having an alicyclic structure in the side chain.

[0085] The amount of the other resin added is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, based on the mass of the A layer being 100%. The other resin is not particularly limited, and conventionally known resins suitable for stretched film applications can be appropriately used in the present invention. Examples thereof include polyolefin resins such as polyethylene, poly(1-butene), polyisobutene, poly(1-pentene), and poly(4-methyl-1-pentene) and copolymer resins thereof, such as ethylene-propylene copolymers, propylene-butene copolymers, ethylene-butene copolymers, and ethylene-(4-methyl-1-pentene) copolymers, and copolymers of α-olefins. Other examples include polystyrene resins, elastomers, polyvinyl resins, polyester resins, polyurethane resins, nylon resins, and copolymers thereof.

[0086] Here, when the other resin is a copolymer containing propylene, the propylene content is less than 50 mass% (for example, 40 mass% or less), preferably 20 mass% or less, and more preferably 10 mass% or less, based on the mass of the other resin being 100 mass%.

[0087] As the other resin, a commercially available product may be used, for example, a copolymer of α-olefins such as Tafmer (registered trademark) (manufactured by Mitsui Chemicals, Inc.) can be mentioned, which can be suitably used for the above-mentioned purpose.

[0088] Layer A can further contain inorganic particles, organic particles, etc., either alone or in combination of two or more kinds. By containing particles, the friction coefficient and surface roughness can be adjusted when the film is made into a stretched film, and a film with a good winding shape without wrinkles can be obtained. In addition, when the stretched film is used for a capacitor, its electrical properties (self-healing properties) can be improved.

[0089] The inorganic particles are not particularly limited, and include, for example, particles of metal oxides such as titanium oxide, zinc oxide, aluminum oxide, magnesium oxide, and silicon compounds such as silica, and can be preferably used. In addition to these, the inorganic particles include, for example, particles of light calcium carbonate, heavy calcium carbonate, kaolin, calcined kaolin, talc, calcium sulfate, barium sulfate, zinc sulfide, zinc carbonate, satin white, aluminum silicate, diatomaceous earth, calcium silicate, magnesium silicate, alumina, colloidal alumina, boehmite, pseudoboehmite, aluminum hydroxide, magnesium carbonate, magnesium hydroxide, zeolite, smectite, and the like. The organic particles include resin particles made of crosslinkable resin, silicone resin particles, and the like.

[0090] The average particle size of the particles is, for example, 0.05 μm or more and 2.0 μm or less. The average particle size is preferably 0.1 μm or more and 1.5 μm or less, and more preferably 0.4 μm or more and 1.2 μm or less. The average particle size of the inorganic particles and the organic particles is measured by the method described in the Examples below.

[0091] As the particles, commercially available products may be used, such as SeaHostar (registered trademark) (manufactured by Nippon Shokubai Co., Ltd.), which can be suitably used for the above-mentioned purpose.

[0092] The particle content is, for example, 0.1% by mass to 2.0% by mass, preferably 0.2% by mass to 1.5% by mass, and more preferably 0.3% by mass to 1.2% by mass, with the mass of Layer A being 100% by mass.

[0093] The A layer may further contain an antioxidant. The antioxidant is mainly used for the following two purposes. One purpose is to suppress thermal and oxidative deterioration of the resin in the film-forming extruder and / or melt kneader, and the other purpose is to suppress the deterioration of physical properties such as strength due to deterioration during long-term use of the stretched film. An example of the latter is, for example, to contribute to suppression of deterioration during long-term use and maintenance of the electrical properties of the capacitor when used for a capacitor. An antioxidant that mainly contributes to the former purpose is also called a "primary agent", and an antioxidant that mainly contributes to the latter purpose is also called a "secondary agent". Two or more types of antioxidants may be used for these two purposes, or one type of antioxidant may be used for both purposes.

[0094] An example of a primary agent is 2,6-di-tertiary-butyl-para-cresol (common name: BHT). This antioxidant is mostly oxidized, decomposed or evaporated in the extruder, and almost none remains after the film is stretched. Therefore, when layer A after stretching contains BHT, the content is usually less than 100 ppm by mass, with the mass of layer A being 100%.

[0095] Examples of the secondary agent include hindered phenol-based antioxidants having a carbonyl group. Among the hindered phenol-based antioxidants, examples of the hindered phenol-based antioxidants having a carbonyl group include triethylene glycol-bis[3-(3-tertiary butyl-5-methyl-4-hydroxyphenyl)propionate] (trade name: Irganox 245), 1,6-hexanediol-bis[3-(3,5-di-tertiary butyl-4-hydroxyphenyl)propionate] (trade name: Irganox 259), pentaerythritol tetrakis[3-(3,5-di-tertiary butyl-4-hydroxyphenyl)propionate] (trade name: Irganox 1010), 2,2-thiazole-bis[3-(3,5-di-tertiary butyl-4-hydroxyphenyl)propionate] (trade name: Irganox 1020), and 2,2-thiazole-bis[3-(3,5-di-tertiary butyl-4-hydroxyphenyl)propionate] (trade name: Irganox 1030). Examples of suitable compounds include N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (trade name: Irganox 1035), octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (trade name: Irganox 1076), and N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxy-hydrocinnamamide) (trade name: Irganox 1098). Of these, pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) is particularly preferred, due to its excellent heat resistance. (Here, all of the Irganox (registered trademark) products are manufactured by BASF Japan Ltd.)

[0096] When Layer A contains one or more types of hindered phenol-based antioxidants, the total content thereof is preferably from 1000 to 7000 ppm by mass, more preferably from 2000 to 6000 ppm by mass, based on 100% by mass of Layer A, from the viewpoint of appropriate effect development. Note that the hindered phenol-based antioxidant is partially oxidized and decomposed during the extrusion process during the production of a stretched film, and the remaining amount when the film is made into a stretched film is generally 60 to 80% by mass of the above-mentioned content.

[0097] The A layer may further contain additives. Examples of additives include nucleating agents, chlorine absorbents, lubricants, plasticizers, flame retardants, colorants, etc. The content of the additives in the A layer is, for example, 0% by mass or more and 10% by mass or less, 0% by mass or more and 5% by mass or less, 0% by mass or more and 1% by mass or less, 0% by mass or more and 0.5% by mass or less, or 0% by mass or more and 0.1% by mass or less. The substantial lower limit is about 0.01% by mass.

[0098] The thickness of the A layer of the present invention is not particularly limited. The preferred thickness depends on the application, but for example, in packaging applications, separator applications, etc., 5 μm to 80 μm, 10 μm to 50 μm are preferably used. In capacitor applications, from the viewpoint of reducing the volume of the capacitor and increasing the electrostatic capacitance, the thinner the thickness, the better. From this viewpoint, it is preferably 10 μm or less, more preferably 9 μm or less, even more preferably 8 μm or less, even more preferably 6 μm or less, particularly preferably 5 μm or less, especially more preferably 4 μm or less, and particularly preferably 3 μm or less. In addition, from the viewpoint of stretchability and metal vapor deposition process, it is, for example, 1 μm or more, preferably 1.5 μm or more, more preferably 1.8 μm or more, even more preferably 2 μm or more, and even more preferably 2.2 μm or more after stretching.

[0099] 1-4. Stretched Film The stretched film of the present invention has Layer A containing 55% by mass or more and 99% by mass or less of a polypropylene-based resin and 1% by mass or more and 45% by mass or less of a polymer having an alicyclic structure in a side chain, where the mass of Layer A is 100% by mass, and the Layer A is stretched in at least one direction.

[0100] The stretched film of the present invention may be a single-layer stretched film consisting of Layer A, or may be a multilayer film obtained by laminating a plurality of layers and / or films using a conventionally known lamination method, such as a coextrusion method, a lamination method, a heat sealing method, a coating method, etc., either alone or in combination. The lamination may be performed before or after stretching Layer A.

[0101] The multilayer film may have a three-layer structure of layer b / layer a / layer b consisting of a surface layer (skin layer: layer b) and a core layer (layer a), a three-layer structure of layer b / layer a / layer c in which one surface layer is further another layer (layer c), a four-layer structure of layer b / layer a / layer a / layer c in which there are two core layers, a four-layer structure of layer b / layer a / layer a' / layer c in which one core layer is the other core layer (layer a'), a layer b / layer d / layer a / layer d / layer b in which an intermediate layer is also placed, or a so-called super multilayer film including a two or more layer structure in which two or more layers of layer a are laminated, or a laminate structure in which ten or more layers of layer a are laminated. Each layer to be laminated may be made of a different resin or the same resin.

[0102] The Layer A of the present invention can be used as any of Layer a, Layer a', Layer b, Layer c, Layer d, etc. For example, when used as a surface layer, it tends to have excellent stretchability, and when used as a core layer, it tends to have excellent rigidity and insulation properties at high temperatures.

[0103] In order to easily realize the effects of the present invention, the thickness ratio of layer A to the stretched film of the present invention is preferably 50% or more, more preferably 60% or more, even more preferably 70% or more, and particularly preferably 80% or more, relative to 100% of the thickness of the stretched film.

[0104] When the layer A of the present invention is used as a core layer, a preferred example of a surface layer to be laminated is a layer containing a polypropylene resin as a main component and a pigment. The polypropylene resin and pigment may be the same as those of the layer A.

[0105] The preferred layer structure depends on the application, but for example, in packaging applications, separator applications, etc., two or more layers are preferred from the viewpoint of functional separation between the core layer and the skin layer. In capacitor applications, a single layer is preferred from the viewpoint of reducing the thickness, and two or more layers are preferred from the viewpoint of electrical insulation.

[0106] Specific examples of coextrusion methods include pre-die lamination, in which molten resins are brought into contact in a feed block before the die, in-die lamination, in which they are brought into contact along a path inside the die, and out-die lamination, in which they are discharged from multiple concentric lips and brought into contact, etc. For example, in the case of in-die lamination, a multi-layer die such as a three-layer multi-manifold die can be used.

[0107] The thickness of the stretched film of the present invention is not particularly limited. The preferred thickness depends on the application, but for example, for packaging applications, separator applications, etc., 5 μm to 80 μm, 10 μm to 50 μm are preferably used. For capacitor applications, from the viewpoint of reducing the volume of the capacitor and increasing the electrostatic capacitance, the thinner the film, the more preferable. From this viewpoint, the thickness is preferably 10 μm or less, more preferably 9 μm or less, even more preferably 8 μm or less, even more preferably 6 μm or less, particularly preferably 5 μm or less, especially more preferably 4 μm or less, and particularly preferably 3 μm or less. In addition, from the viewpoint of stretchability and metal vapor deposition process, the thickness after stretching is, for example, 1 μm or more, preferably 1.5 μm or more, more preferably 1.8 μm or more, even more preferably 2 μm or more, and even more preferably 2.2 μm or more.

[0108] The thickness of the film of the present invention, such as the unstretched film of the present invention or the biaxially stretched film of the present invention, is measured using an outside micrometer (high-precision digital micrometer MDH-25MB, manufactured by Mitutoyo Corporation) in accordance with JIS K 7130:1999 Method A.

[0109] The stretched film of the present invention has high dielectric breakdown strength at high temperatures, which is measured in environments of 120° C. and 135° C. according to the method described in the Examples below.

[0110] The dielectric breakdown strength of the stretched film of the present invention in a 120° C. environment is preferably 450 V DC / μm or more, preferably 470V DC / μm or more, more preferably 490V DC / μm or more, especially preferably 500V DC / μm or more, more particularly preferably 510V DC The upper limit of the dielectric breakdown strength at each of the above temperatures is not particularly limited, and is, for example, 700V DC / μm or less, 650V DC / μm or less.

[0111] The dielectric breakdown strength of the film of the present invention in a 135° C. environment is preferably 420 V DC / μm or more, preferably 440V DC / μm or more, more preferably 460V DC / μm or more, especially preferably 480V DC / μm or more, more particularly preferably 490V DC The upper limit of the dielectric breakdown strength at each of the above temperatures is not particularly limited, and is, for example, 650V DC / μm or less, 600V DC / μm or less.

[0112] The stretched film of the present invention is preferable because the change in dielectric breakdown strength due to temperature rise is small. The dielectric strength maintenance rate (%), which is the ratio of the dielectric breakdown strength in a 135°C environment to the dielectric breakdown strength in a 120°C environment (dielectric breakdown strength in a 135°C environment / dielectric breakdown strength in a 120°C environment), is preferably 87% or more, more preferably 88% or more, even more preferably 89% or more, and particularly preferably 90% or more. There is no particular upper limit, and it is, for example, 100%, 99%, or 98%. Note that the load related to the dielectric breakdown strength is significantly different between the 120°C environment and the 135°C environment. Therefore, the dielectric strength maintenance rate of a general polypropylene film is small, and the temperature stability of the electrical properties of a capacitor using the film is reduced, which is not preferable. The stretched film of the present invention is preferable because the change in dielectric breakdown strength is suppressed from the 120°C environment to the 135°C environment, and the temperature stability of the electrical properties of a capacitor using the film is improved.

[0113] The stiffness of the stretched film of the present invention in a high-temperature environment is represented by the elongation rate measured by a thermo-mechanical analyzer (TMA) according to the method described in the Examples below. The stiffness of the stretched film is preferably small when the temperature is raised from room temperature to 130° C., and the elongation rate is preferably 4.5% or less, more preferably 4% or less, even more preferably 3.5% or less, and particularly preferably 3% or less. By setting the elongation rate to 5% or less, the stiffness of the stretched film at high temperatures is maintained high. In addition, the electrical insulation at high temperatures is also excellent, which is preferable because the temperature stability of the electrical properties of the capacitor using the stretched film is improved. The lower limit of the elongation rate is, for example, 0.2% or more, 0.5% or more, or 1% or more. By setting it to 0.2% or more, the stretchability of the film is easily improved.

[0114] The stretched film of the present invention has high post-processing passability. When the stretched film of the present invention is used for a capacitor, the post-processing is mainly a deposition step for laminating a metal layer. The deposition passability is measured according to the method of the examples described later. The stretched film of the present invention can be subjected to deposition without film breakage even at a high deposition speed of, for example, 150 m / min.

[0115] The use of the stretched film of the present invention is not particularly limited. For example, the film of the present invention can be used as a packaging film or a separator having excellent heat resistance by taking advantage of its heat resistance. In addition, the stretched film of the present invention can be suitably used as a film for a capacitor. In particular, it can be very suitably used for a capacitor that is used in a high-temperature environment of 120° C. or more, and is small in size and has a high capacity (for example, 5 μF or more, preferably 10 μF or more, and more preferably 20 μF or more).

[0116] 1-5. Manufacturing method of stretched film The raw material of the stretched film of the present invention (including at least the polypropylene resin and the polymer having an alicyclic structure in the side chain) is dried before use if it contains a large amount of water. The drying conditions are not particularly limited, but are, for example, 70 to 150°C, preferably 80 to 130°C. The drying time can be appropriately adjusted depending on the drying temperature, and is, for example, 2 to 30 hours, preferably 3 to 20 hours.

[0117] The raw materials may be individually fed into the film-forming extruder and mixed inside the film-forming extruder, or may be mixed before being fed into the film-forming extruder and then fed into the film-forming extruder as a raw material mixture.

[0118] The mixing method for preparing the raw material mixture is not particularly limited, but may be a method in which a plurality of types of resin masses (pellets, etc.) are dry-blended using a mixer or the like.

[0119] As a mixing method, melt kneading (melt blending) may be used. Melt kneading is preferable because if the resin can be uniformly kneaded, the rigidity, electrical insulation property, stretchability, etc. of the stretched film are likely to be improved.

[0120] As a method of melt kneading, a melt kneader of a single screw type, a twin screw type, or a multi-screw type having more than one screw can be used. Among them, a twin screw type melt kneader is preferably used because it has a high effect of improving the rigidity, electrical insulation, stretchability, etc. of the stretched film. In the case of a twin screw type, both a kneading type of the same direction rotation and a kneading type of the opposite direction rotation can be used, but from the viewpoint of suppressing resin deterioration, a same direction rotation is preferable. The ratio of the diameter and length of the screw of the melt kneader (L / D) is preferably 20 or more, more preferably 25 or more, and even more preferably 28 or more. By making L / D 20 or more, the resin is well mixed, and the rigidity, electrical insulation, and stretchability of the stretched film are improved. There is no upper limit to L / D, but from the viewpoint of suppressing resin deterioration, it is 80 or less, preferably 50 or less.

[0121] The temperature during melt kneading is preferably 200° C. to 300° C., more preferably 220° C. to 280° C., in order to balance the suppression of resin deterioration and kneadability. During melt kneading, it is preferable to purge the kneader with an inert gas such as nitrogen in order to suppress the deterioration of the resin.

[0122] The raw material and / or raw material mixture of the present invention is supplied to a film-forming extruder and extruded. The method of extrusion is not particularly limited, and a known extrusion method can be adopted. For example, the solid raw material or resin composition of the present invention supplied to the film-forming extruder is mixed by a screw in a heated molten state, filtered through a filter, extruded into a film form from a die such as a single-layer T die, and solidified by contact with a cooling roll set to a predetermined surface temperature to obtain the unstretched film of the present invention.

[0123] Examples of the extruder for film production include a single screw type, a twin screw type, and a multi-screw type having three or more screws. In the case of twin or more screws, the type of screw rotation may be, for example, a same-direction rotation or a counter-direction rotation. The melting temperature is preferably 200 to 300°C, preferably 230 to 280°C, and more preferably 240 to 275°C. This allows the resin to be appropriately kneaded, and the rigidity, electrical insulation, stretchability, etc. of the stretched film are likely to be improved. In order to suppress deterioration during melt extrusion of the resin, it is preferable to purge the extruder with an inert gas such as nitrogen.

[0124] The filtration accuracy of the filter for filtering the resin of the present invention in a molten state is not particularly limited, but is, for example, 2 to 30 μm, preferably 5 to 25 μm, and more preferably 10 to 25 μm.

[0125] The temperature of the die is not particularly limited, but is preferably 200 to 300°C, preferably 210 to 280°C, more preferably 215 to 270°C, and further preferably 220 to 260°C.

[0126] The method of contacting the molten resin of the present invention extruded from a die with a cooling roll to solidify it is not particularly limited, and examples thereof include air knife, electrostatic pinning, elastic roll nip, metal roll nip, elastic metal roll nip, etc. The surface temperature of the cooling roll is, for example, 30 to 130°C, preferably 35 to 120°C, and more preferably 40 to 110°C.

[0127] The draft ratio when the resin of the present invention in a molten state extruded from a die is brought into contact with a cooling roll is preferably 1 to 20, more preferably 1.1 to 16, more preferably 1.2 to 10, and even more preferably 1.3 to 8. By setting the draft ratio within this range, the longitudinal orientation of the stretched film can be set in an appropriate range, and the stretchability can be improved. The draft ratio is determined based on the density d (g / cm) of the molten resin. 3 ), width W (cm) of the die lip outlet, average slit gap t (cm) of the die lip outlet, resin discharge rate Q (g / min), and peripheral speed V (cm / min) of the cooling and forming roll, using the following formula. Draft ratio = dVWt / Q

[0128] The thickness of the unstretched film of the present invention is not particularly limited, but is, for example, 20 to 300 μm.

[0129] The method of stretching the unstretched film of the present invention is not particularly limited, and known stretching methods can be adopted. For example, the method of stretching the unstretched film of the present invention in the longitudinal direction (machine direction, MD) by heating it with a heating roll (longitudinal uniaxial roll stretching method); the method of stretching the unstretched film of the present invention in the transverse direction (width direction, TD) in an oven (generally called a tenter) at a predetermined temperature (transverse uniaxial stretching method); the method of performing transverse uniaxial stretching after longitudinal uniaxial roll stretching (sequential biaxial stretching method); the method of performing transverse uniaxial stretching after longitudinal uniaxial roll stretching and further performing longitudinal uniaxial (roll or tenter method) stretching (multistage sequential biaxial stretching method); the method of performing longitudinal and transverse stretching of the unstretched film of the present invention in a tenter at a predetermined temperature (tenter method sequential biaxial stretching method); the method of simultaneously performing longitudinal and transverse stretching of the unstretched film of the present invention in a tenter (simultaneous biaxial stretching method); and the like. As a method for stretching the unstretched film of the present invention, a method in which longitudinal uniaxial roll stretching is followed by transverse uniaxial stretching (sequential biaxial stretching method) is preferred because it provides a stretched film with excellent rigidity, electrical insulation, stretchability, etc.

[0130] In the longitudinal uniaxial roll stretching method, a plurality of heating rolls may be used. The stretching point may be one or two or more. When there is one stretching point, the temperature of the roll immediately before the stretching point (roll before stretching) (T MD ), and when there are two or more stretching points, the surface temperature of the roll before stretching at the point where the stretch ratio is maximum (T MD ) is preferably 125° C. or more and 175° C. or less, more preferably 130° C. or more and 170° C. or less, even more preferably 135° C. or more and 168° C. or less, and particularly preferably 140° C. or more and 166° C. or less. The stretching ratio in the longitudinal direction (the product of the stretching points when there are two or more stretching points) is preferably 1.5 times or more and 5.0 times or less, more preferably 2.0 times or more and 4.6 times or less, and even more preferably 2.2 times or more and 4.2 times or less. By setting the temperature and stretching ratio in the above temperature ranges, the orientation in the longitudinal direction is suppressed within an appropriate range, and a stretched film excellent in stiffness, electrical insulation, stretchability, etc. can be easily obtained.

[0131] The tenter of the present invention is preferably one having three or more temperature zones, and more preferably one having five or more temperature zones, so that heating, stretching, and the later-described heat treatment, relaxation treatment, cooling treatment, etc. can be performed at different temperatures.

[0132] When longitudinal stretching is performed in a tenter, the oven temperature during stretching (T MD ) is preferably 125° C. or more and 175° C. or less, more preferably 130° C. or more and 170° C. or less, even more preferably 135° C. or more and 168° C. or less, and particularly preferably 140° C. or more and 166° C. or less. The stretching ratio in the longitudinal direction is preferably 1.5 times or more and 5.0 times or less, more preferably 2.0 times or more and 4.6 times or less, and even more preferably 2.2 times or more and 4.2 times or less.

[0133] When transverse stretching is performed in a tenter, the oven temperature during stretching (T TD ) is preferably 140° C. or higher and 175° C. or lower, more preferably 145° C. or higher and 170° C. or lower, even more preferably 150° C. or higher and 168° C. or lower, and particularly preferably 155° C. or higher and 166° C. or lower. The stretching ratio in the transverse direction is preferably 5.0 times or higher and 11.0 times or lower, more preferably 6.0 times or higher and 10.0 times or lower, and even more preferably 7.0 times or higher and 9.5 times or lower. By setting the temperature and stretching ratio in these ranges, the orientation in the transverse direction is suppressed within an appropriate range, and a stretched film excellent in stiffness, electrical insulation, stretchability, etc. can be easily obtained.

[0134] The above-mentioned stretching temperature (T MD、 and T TD It is more preferable that Tg is adjusted according to the glass transition temperature (Tg) of the polymer having an alicyclic structure in the side chain contained in the layer A of the present invention. MD is preferably Tg-10°C or more and Tg+25°C or less, more preferably Tg-5°C or more and Tg+20°C or less, and even more preferably Tg or more and Tg+16°C or less. TDis preferably Tg or more and Tg+30° C. or less, more preferably Tg+5° C. or more and Tg+28° C. or less, and even more preferably Tg+10° C. or more and Tg+25° C. or less. By setting the temperature within this range, the orientation of the stretched film is controlled within an appropriate range, and a stretched film excellent in stiffness, electrical insulation, stretchability, etc. can be easily obtained.

[0135] In addition, the aforementioned stretching temperature (T MD and T TD If the temperature is below the above-mentioned range, if the kneading properties during resin blending or extrusion are poor, or if the draft ratio during extrusion molding is inappropriate, pores may form in layer A during stretching. If many pores form, the rigidity, electrical insulation, and stretchability of the stretched film tend to decrease.

[0136] Since the total light transmittance of the stretched film is likely to decrease when many pores are generated, the total light transmittance of the stretched film of the present invention is preferably 80% or more, more preferably 85% or more, even more preferably 88% or more, and particularly preferably 90% or more. From the viewpoint of the electrical characteristics (safety) of the capacitor, the total light transmittance is preferably 99% or less, more preferably 98% or less, even more preferably 97% or less, and particularly preferably 96% or less.

[0137] The product of the longitudinal stretching ratio and the transverse stretching ratio of the stretched film (when the relaxation treatment described below is performed, the product is calculated using the longitudinal stretching ratio before relaxation and the transverse stretching ratio before relaxation) is preferably 15 to 48, more preferably 17 to 42, even more preferably 19 to 38, particularly preferably 21 to less than 35, and more particularly preferably 22 to 34. By setting the temperature and stretching ratio within the above ranges, a stretched film excellent in rigidity, electrical insulation, stretchability, etc. can be easily obtained.

[0138] Stretched films with an area ratio of 12% or less and unstretched films (area ratio of 1%) tend to have low rigidity and electrical insulation. Also, if the area ratio at which a film can be stretched without breaking is 12% or less, the stretchability is not very good.

[0139] The stretched film of the present invention may be subjected to a relaxation treatment (a treatment for reducing the stretch ratio after stretching, for example, by 20% or less of the stretch ratio), a heating treatment, or a cooling treatment, if necessary. These treatments may be performed independently or in combination, for example, by performing a relaxation treatment and a heating treatment simultaneously, or a relaxation treatment and a cooling treatment simultaneously. By appropriately performing the relaxation treatment, heating treatment, and cooling treatment, the flatness of the stretched film, dimensional stability against temperature changes, and passability through the deposition process can be improved.

[0140] The relaxation in the transverse direction is preferably from 3% to 20%, more preferably from 5% to 16%, and even more preferably from 6.5% to 14%, relative to the maximum ratio of transverse stretching.

[0141] The heat treatment temperature is preferably from 150° C. to 180° C., more preferably from 155° C. to 175° C., and further preferably from 160° C. to 172° C. The heat treatment time is preferably from 1 second to 20 seconds, and more preferably from 2 seconds to 15 seconds.

[0142] The stretched film of the present invention may be subjected to corona treatment, static electricity removal treatment, heating treatment, etc. By appropriately carrying out corona treatment, static electricity removal treatment, heating treatment, etc., it is possible to improve the passability through the deposition process. The heating treatment temperature is preferably 20°C or more and 80°C or less, more preferably 25°C or more and 60°C or less, and even more preferably 30°C or more and 55°C or less. The heating treatment time is preferably 3 hours or more and 50 hours or less, and more preferably 6 hours or more and 30 hours or less.

[0143] 2. Metal Laminated Film In one aspect, the present invention relates to a metal laminated film (sometimes referred to as the "metal laminated film of the present invention" in this specification) having the stretched film of the present invention and a metal layer laminated on one or both sides of the stretched film. This will be described below.

[0144] The stretched film of the present invention may have a metal layer on one or both sides for adjusting the permeability of gases such as oxygen and water vapor when used as a packaging film, or as an electrode when used as a capacitor.

[0145] Examples of methods for laminating a metal layer on the surface of the stretched film of the present invention include vacuum plating such as metal vapor deposition and sputtering, coating and drying of a metal-containing paste, and pressure bonding of metal foil or metal powder. Among these, from the viewpoints of productivity and economy, the vacuum vapor deposition method and the sputtering method are more preferred, and the vacuum vapor deposition method is even more preferred. Examples of the vacuum vapor deposition method include the crucible method and the wire method in general, but are not particularly limited, and the most suitable method can be selected as appropriate.

[0146] The metal used in the metal layer may be, for example, a single metal such as zinc, lead, silver, chromium, aluminum, copper, or nickel, a mixture of two or more of these, or an alloy of these. In consideration of the environment, economy, and performance, one or more of zinc and aluminum are preferred.

[0147] The film resistance of the metal layer is preferably about 0.5 to 10 Ω / □ from the viewpoint of permeability to gases such as oxygen and water vapor, and about 1 to 60 Ω / □ from the viewpoint of the electrical properties of the capacitor. From the viewpoint of the electrical properties of the capacitor, in order to realize self-healing properties, the film resistance is more preferably 5 Ω / □ or more, and even more preferably 10 Ω / □ or more, and from the viewpoint of safety as a capacitor, the film resistance is more preferably 50 Ω / □ or less, and even more preferably 30 Ω / □ or less.

[0148] When forming an electrode (metal vapor deposition film) by vacuum deposition, the film resistance can be measured during deposition, for example, by a non-contact eddy current method or light transmittance method known to those skilled in the art. The film resistance of the metal vapor deposition film can be adjusted, for example, by adjusting the output of the evaporation source to adjust the amount of evaporation.

[0149] In capacitor applications, when a metal vapor deposition film is formed on one side of a stretched film, an insulating margin (vertical margin) of a certain width where no metal is laminated is formed so that it will become an insulating part when the film is rolled up to make a capacitor.

[0150] Furthermore, in order to strengthen the bond between the metal layer of the metal layer-integrated film and the metallikon electrode, it is preferable to form a heavy edge portion. The film resistance of the heavy edge portion is usually about 1 to 8 Ω / □, and preferably about 1 to 5 Ω / □. The thickness of the metal film of the heavy edge portion is not particularly limited, but is preferably 1 to 200 nm.

[0151] In capacitor applications, the deposition pattern (fuse pattern) of the metal deposition film to be formed is not particularly limited, but from the viewpoint of improving the characteristics such as safety of the capacitor, it is preferable to form fuses as pattern deposition such as a fishnet pattern, T-margin pattern, etc. When a metal deposition film having a deposition pattern including fuses is formed on at least one side of the stretched film of the present invention, the safety of the obtained capacitor is improved, and it is also effective and preferable from the viewpoint of preventing breakdown and short circuit of the capacitor.

[0152] As a method for forming the fuse and the insulating margin, any known method can be used without any restrictions, such as a tape method in which masking is performed with tape during deposition, or an oil method in which masking is performed by applying oil.

[0153] A protective agent may be applied onto the metal laminated film of the present invention for the purpose of physical protection of the metal layer, prevention of moisture absorption, prevention of oxidation, etc. As the protective agent, silicone oil, fluorine oil, etc. can be preferably used. The protective agent may be provided as a layer on the metal layer, or may be impregnated into the metal layer.

[0154] The metal laminated film of the present invention can be processed into the capacitor of the present invention described below. The metal laminated film of the present invention can also be used for packaging purposes, for example as a barrier film against oxygen and other gases.

[0155] 3. Film Capacitors In one aspect, the present invention relates to a film capacitor (sometimes referred to as "the capacitor of the present invention" in this specification) including the stretched film of the present invention or the metal laminated film of the present invention. This will be described below.

[0156] In such capacitors, the stretched film of the present invention can be used as a dielectric film for a capacitor by, for example, (i) using the above-mentioned metal laminated film, (ii) laminating the stretched film of the present invention not provided with electrodes with a dielectric having both sides metallized (the dielectric can be, for example, the stretched film of the present invention or another plastic film), or (iii) laminating the stretched film of the present invention not provided with electrodes with another conductor (for example, a metal foil).

[0157] In the process of producing a capacitor, a film is wound. For example, two pairs of the metal laminated films of the present invention are overlapped and wound so that the metal layers of the metal laminated film of the present invention and the stretched film of the present invention are alternately laminated, and further, the insulating margins are on opposite sides. In this case, it is preferable to laminate the two pairs of the metal laminated films of the present invention with a shift of 1 to 2 mm. The winding machine used is not particularly limited, and for example, an automatic winding machine 3KAW-N2 type manufactured by Kaito Seisakusho Co., Ltd. can be used.

[0158] The film winding process is not limited to the above-mentioned method, and other methods may be used, for example, a double-sided vapor-deposited stretched film of the present invention (in which case the heavy edges are arranged at the opposite ends of the front and back surfaces) and a non-vapor-deposited stretched film of the present invention (2 to 3 mm narrower than the double-sided vapor-deposited stretched film of the present invention) may be alternately laminated and wound.

[0159] When producing a flat capacitor, the resulting wound product is usually pressed after winding. Pressing promotes tightening of the capacitor and element formation. From the viewpoint of controlling and stabilizing the interlayer gap, the optimum pressure to be applied varies depending on the thickness of the stretched film of the present invention, and is generally 2 to 20 kg / cm. 2 It is.

[0160] Next, metal is sprayed onto both end faces of the winding to provide metallikon electrodes, thereby completing a capacitor.

[0161] The capacitor is further subjected to a predetermined heat treatment. That is, the present invention includes a step of subjecting the capacitor to a heat treatment (hereinafter, sometimes referred to as "thermal aging"). The heat treatment temperature is not particularly limited, but is, for example, 80 to 190°C. The method of subjecting the capacitor to heat treatment may be appropriately selected from known methods including, for example, a method using a thermostatic bath under a vacuum atmosphere or a method using high-frequency induction heating. The time for which the heat treatment is performed is preferably 1 hour or more, more preferably 5 hours or more, from the viewpoint of obtaining mechanical and thermal stability, but is more preferably 20 hours or less, from the viewpoint of preventing molding defects such as heat wrinkles and molding.

[0162] By carrying out the heat treatment, the effect of thermal aging can be obtained. Specifically, the gap between the films constituting the capacitor based on the stretched film of the present invention is reduced, corona discharge is suppressed, and the internal structure of the stretched film of the present invention changes and crystallization proceeds. As a result, it is considered that the electrical insulation is improved. If the temperature of the heat treatment is lower than a predetermined temperature, the above-mentioned effect of thermal aging cannot be sufficiently obtained. On the other hand, if the temperature of the heat treatment is higher than the predetermined temperature, the stretched film of the present invention may undergo thermal decomposition, oxidative deterioration, etc.

[0163] Lead wires or bus bars are usually welded to the metallikon electrodes of the heat-aged capacitor. In order to impart weather resistance, particularly to prevent humidity degradation, the capacitor is preferably encapsulated in a case and potted with epoxy resin.

[0164] The capacitor of the present invention using the stretched film of the present invention can be suitably used in high-temperature environments, and can be made into a small-sized capacitor with a high capacity (for example, 5 μF or more, preferably 10 μF or more, and more preferably 20 μF or more). Therefore, the capacitor of the present invention can be used as a high-voltage capacitor used in electronic devices, electric devices, etc.; various switching power supplies; filter capacitors for converters, inverters, etc., smoothing capacitors, etc. Furthermore, the capacitor of the present invention can be suitably used as an inverter capacitor, converter capacitor capacitor, etc. for controlling the drive motor of electric vehicles, hybrid vehicles, etc., which have seen an increase in demand in recent years. EXAMPLES

[0165] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the examples.

[0166] (1)Measurement method The various measurement methods are as follows.

[0167] (1-1) Number average molecular weight (Mn), weight average molecular weight (Mw), z-average molecular weight (Mz), molecular weight distribution (Mw / Mn), and molecular weight distribution (Mz / Mw) of polypropylene resin Using GPC (gel permeation chromatography) under the following conditions, the number average molecular weight (Mn), weight average molecular weight (Mw), z-average molecular weight (Mz), molecular weight distribution (Mw / Mn), and molecular weight distribution (Mz / Mw) of each resin were measured.

[0168] Specifically, a high-temperature GPC device with a built-in differential refractometer (RI), HLC-8121GPC-HT model, manufactured by Tosoh Corporation, was used. Three TSKgel GMHHR-H(20)HT columns manufactured by Tosoh Corporation were connected and used as columns. Measurements were performed at a column temperature of 140°C, with trichlorobenzene as the eluent flowing at a flow rate of 1.0 ml / min. A calibration curve for the molecular weight M was created using standard polystyrene manufactured by Tosoh Corporation, and the measured values ​​were converted to the molecular weight of polypropylene using the Q-factor to obtain the number average molecular weight (Mn), weight average molecular weight (Mw), and z-average molecular weight (Mz). The molecular weight distribution (Mw / Mn) was obtained using the values ​​of Mw and Mn. The molecular weight distribution (Mz / Mw) was also obtained using the values ​​of Mz and Mw.

[0169] (1-2) Mesopentad fraction of polypropylene resin A polypropylene resin was dissolved in a solvent, and the properties were measured using a high-temperature Fourier transform nuclear magnetic resonance spectrometer (high-temperature FT-NMR) under the following conditions. High-temperature nuclear magnetic resonance (NMR) instrument: JEOL Ltd., high-temperature Fourier transform nuclear magnetic resonance instrument (high-temperature FT-NMR), JNM-ECP500 Observed nucleus: 13C (125MHz) Measurement temperature: 135℃ Solvent: ortho-dichlorobenzene (ODCB: mixed solvent of ODCB and deuterated ODCB (mixing ratio = 4 / 1)) Measurement mode: Single pulse proton broadband decoupling Pulse width: 9.1μsec (45° pulse) Pulse interval: 5.5sec Number of times: 4,500 Shift criteria: CH 3 (mmmm)=21.7ppm The mesopentad fraction, which indicates the degree of stereoregularity, was calculated as a percentage (%) from the integral intensity of each signal derived from a combination of five pentads (pentads) consisting of meso (m) pentads arranged in the same direction and racemo (r) pentads arranged in the opposite direction (mmmm, mrrm, etc.). The assignment of each signal derived from mmmm, mrrm, etc. was based on the spectral descriptions in, for example, T. Hayashi et al., Polymer, Vol. 29, p. 138 (1988).

[0170] (1-3) Heptane insolubles (HI) of polypropylene resins Polypropylene resin was press-molded to 10mm x 35mm x 0.3mm to prepare a measurement sample weighing approximately 3g. Next, approximately 150mL of heptane was added and Soxhlet extraction was performed for 8 hours. The heptane insoluble matter was calculated from the sample mass before and after extraction.

[0171] (1-4) Melt mass flow rate of resin The melt flow rate (MFR) of each resin in the form of raw resin pellets was measured in accordance with JIS K 7210-1:2014 using a melt indexer manufactured by Toyo Seiki Co., Ltd. Specifically, 4 g of raw material was inserted into a cylinder set at a test temperature (230°C for polypropylene resins, 260°C for polymers having an alicyclic structure in the side chain and polymers having an alicyclic structure in the main chain), and preheated for 3.5 minutes under a load of 2.16 kg. The weight of the raw material resin extruded from the bottom hole in 30 seconds was then measured, and the MFR (g / 10 min) was calculated. The above measurement was repeated three times, and the average value was taken as the measured MFR.

[0172] (1-5) Melting point and glass transition temperature of resin The calculation was performed using a Perkin-Elmer input compensation type DSC, DiamondDSC, as follows. 5 mg of each resin was weighed out, packed into an aluminum sample holder, and set in the DSC device. Under nitrogen flow, the temperature was raised from 30°C to 230°C at a rate of 20°C / min, held at 230°C for 5 minutes, cooled to 30°C at 20°C / min, and held at 30°C for 5 minutes. The melting point and glass transition temperature were obtained from the DSC curve when the temperature was raised again to 230°C at 20°C / min. In detail, the melting peak (the maximum melting peak when multiple melting peaks are shown) specified in 9.1(1) of JIS-K7121 was taken as the melting point, and the midpoint glass transition temperature specified in 9.3(1) of JIS-K7121 was taken as the glass transition temperature.

[0173] (1-6) Average particle size of particles The average particle size of the particles was measured as follows. The powder was scattered on a sample stage so that the individual particles did not overlap as much as possible, and at least 100 particles were observed at 10,000 to 30,000 times magnification using an ultra-high resolution field emission scanning electron microscope (FE-SEM, Hitachi High-Technologies S-5200) to obtain observation images. The longest diameter of the particles was measured from the observation images using image analysis software, and the measured values ​​were averaged to obtain the average particle size.

[0174] (2) Preparation of resin composition and stretched film (2-1)Resin used etc. [Polypropylene resin] ·Raw material A: Polypropylene resin A1: Isotactic polypropylene resin made by Prime Polymer Co., Ltd. Prime Polypro (registered trademark) MFR: 3.5g / 10min (measurement temperature 230℃, weight 2.16kg) Melting point: 164℃ Mesopentad fraction: 98.6mol% Heptane insolubles: 98.1% by mass Number average molecular weight (Mn): 49000 Weight average molecular weight (Mw): 390000 z average molecular weight (Mz): 1520000 Molecular weight distribution (Mw / Mn): 8.0 Molecular weight distribution (Mz / Mw): 3.9 A2: Isotactic polypropylene resin made by Prime Polymer Co., Ltd. Prime Polypro (registered trademark) MFR: 5.6g / 10min (measurement temperature 230℃, weight 2.16kg) Melting point: 162℃ Mesopentad fraction: 97.4mol% Heptane insolubles: 97.8% by mass Number average molecular weight (Mn): 47000 Weight average molecular weight (Mw): 270000 z average molecular weight (Mz): 750000 Molecular weight distribution (Mw / Mn): 5.7 Molecular weight distribution (Mz / Mw): 2.8 Raw material B: Polymer with an alicyclic structure in the side chain B1: Made by USI Corporation ViviOn® 0645 Glass transition temperature: 146℃ MFR: 5.5g / 10min (measurement temperature 260℃, 2.16kg weight) Contains a cyclohexane structure in the side chain (The cyclohexane structure is formed by hydrogenating an aromatic ring structure, and the hydrogenation rate is 99 mol% or more.) B2: Made by USI Corporation ViviOn® 1325 Glass transition temperature: 128℃ MFR: 13g / 10min (measurement temperature 260℃, weight 2.16kg) Contains a cyclohexane structure in the side chain (The cyclohexane structure is formed by hydrogenating an aromatic ring structure, and the hydrogenation rate is 99 mol% or more.) Raw material C: Polymer with an alicyclic structure in the main chain C1: Polyplastics Co., Ltd. TOPAS(R)COC6013S-04 Glass transition temperature: 138℃ MFR: 14g / 10min (measurement temperature 260℃, weight 2.16kg) Contains a norbornene structure in the main chain ·Raw material D: Particles D1: Silica particles manufactured by Nippon Shokubai Co., Ltd. SeaHostar(registered trademark) KE-S100 Average particle size: 1.0μm

[0175] (2-2) Method for producing resin composition and stretched film [Examples 1 to 6, Examples 8 to 10, Comparative Examples 1 to 2, and Comparative Example 4] [Preparation of unstretched film] Raw materials A, B, C, and D were weighed out so that each raw material was in the proportions shown in Table 1, and the raw material mixture for layer A obtained by dry blending using a tumbler was fed into a single-screw type film extruder (GM-50, manufactured by GM Engineering Co., Ltd., L / D=32). The raw materials were melted in the extruder set to the melting temperature shown in Table 1, then filtered through a filter with a filtration accuracy of 20 μm, and extruded from a T-die set to 235°C.

[0176] The molten resin was brought into contact with a mirror-finished metal roll (cooling roll) having a surface temperature of 90° C. using an air knife, solidified, and formed into a film to obtain a single-layer unstretched film.

[0177] In this case, the average slit gap t at the die lip outlet of the T-die was changed so that the draft ratio became the value shown in Table 1.

[0178] The thickness of the unstretched film was finely adjusted by changing the extrusion rate and the take-up speed so that the thickness after stretching would reach the target value.

[0179] [Preparation of stretched film] The unstretched film was introduced into a roll-type longitudinal stretching machine, heated sequentially by five preheating rolls, and then heated to the temperature (T MDThe film was heated by a pre-stretch roll whose surface temperature was adjusted to 0.5° C., and uniaxially stretched in the machine direction (MD) at the ratio shown in Table 1. The film was then introduced into a tenter, heated in a preheating zone whose furnace temperature was adjusted to the preheating temperature shown in Table 1, and then heated to the temperature (T TD ), the film was stretched in the transverse direction (TD) at the ratios shown in Table 1 in the stretching zone where the temperature inside the furnace was adjusted to 170°C. The width (transverse direction) was then relaxed by 10% in the heating zone at 170°C. The end of the stretched film coming out of the tenter was slit to a width of 620 mm, and the surface on the side where the air knife was used was subjected to corona treatment, and then wound up to obtain a roll of stretched film. The extrusion amount and take-up speed were finely adjusted so that the thickness of the film was 2.8 μm. The stretchability of the film was good in all of Examples 1 to 6, Examples 8 to 10, Comparative Example 1, and Comparative Example 4. On the other hand, the film of Comparative Example 2 broke when the ratio was increased to the ratio shown above, and the stretchability was not good.

[0180] [Example 7] [Preparation of unstretched film] 75 parts of raw material A1 and 25 parts of raw material B1 were weighed and dry-blended using a tumbler to obtain a raw material mixture for layer A. The mixture was then fed into a single-screw type film extruder (GM-50, manufactured by GM Engineering Co., Ltd., L / D=32). The raw materials were melted in the extruder, which was set at 260°C, and then filtered through a filter with a filtration accuracy of 20 μm, and fed into the core layer (layer A) section of a three-layer multi-die, which was set at 235°C.

[0181] 99.5 parts of raw material A1 and 0.5 parts of raw material D were weighed and dry-blended using a tumbler to obtain a raw material mixture for layer B. The mixture was then fed into a single-screw type film extruder (GM-50, manufactured by GM Engineering Co., Ltd., L / D=32). The raw materials were melted in the extruder, which was set to the melting temperature shown in Table 1, and filtered through a filter with a filtration accuracy of 20 μm. The mixture was then branched into two flow paths and fed to the skin layer (layer B) sections on both sides of a three-layer multi-die, which was set to 235°C.

[0182] The layers were laminated in the order of B layer / A layer / B inside a three-layer multi-die and extruded from the multi-die.

[0183] The three-layer laminated molten resin was brought into contact with a mirror-finished metal roll (cooling roll) with a surface temperature of 90°C using an air knife, solidified, and formed into a film to obtain a three-layer unstretched film.

[0184] In this case, the average slit gap t at the die lip outlet of the multi-die was changed so that the draft ratio was 4.0.

[0185] The thickness of the unstretched film was finely adjusted by changing the extrusion rate and the take-up speed so that the thickness after stretching would reach the target value.

[0186] The extrusion rate was adjusted so that the thickness ratio of each layer of the unstretched film, layer B:layer A:layer B, was 1:1.8:1.

[0187] [Preparation of stretched film] The unstretched film was introduced into a roll-type longitudinal stretching machine, heated sequentially by five preheating rolls, heated by a pre-stretching roll with a surface temperature adjusted to 150 ° C, and uniaxially stretched in the longitudinal direction (MD) at a ratio of 4.0 times. The film was then introduced into a tenter, heated in a preheating zone with an oven temperature adjusted to 170 ° C, and stretched in the transverse direction (TD) at a ratio of 10.0 times in a stretching zone with an oven temperature adjusted to 167 ° C. The width (transverse direction) was then relaxed by 10% in a heating zone set at 170 ° C. The end of the stretched film coming out of the tenter was slit to a width of 620 mm, and the surface on the side where the air knife was used was corona-treated, and then wound up to obtain a roll of stretched film. The extrusion amount and take-up speed were finely adjusted so that the thickness of the film was 2.8 μm. The stretchability of the film of Example 7 was good.

[0188] [Comparative Example 3] 75 parts of raw material A1 and 25 parts of raw material B1 were weighed and dry-blended using a tumbler to obtain a raw material mixture for layer A. The mixture was then fed into a single-screw type film extruder (GM-50, manufactured by GM Engineering Co., Ltd., L / D=32). The raw materials were melted in the extruder, which was set at 260°C, and then filtered through a filter with a filtration accuracy of 20 μm, and extruded from a T-die, which was set at 235°C.

[0189] The molten resin was brought into contact with a mirror-finished metal roll (cooling roll) having a surface temperature of 90° C. using an air knife, solidified, and formed into a film to obtain a single-layer unstretched film.

[0190] In this case, the average slit gap t at the die lip outlet of the T-die was changed so that the draft ratio was 40.

[0191] The extrusion rate and take-up speed were adjusted so that the thickness of the unstretched film was 5 μm.

[0192] The unstretched film was slit at its end to a width of 620 mm, and the surface on which the air knife was used was subjected to corona treatment, after which it was wound up to obtain a roll of unstretched film. In this way, a roll of unstretched film was obtained as a comparative product in Comparative Example 3.

[0193] [Table 1]

[0194] (3) Measurement and evaluation of the physical properties and characteristics of stretched films (3-1) Measurement of total light transmittance The total light transmittance of the stretched films obtained in the examples and comparative examples (however, Comparative Example 3 is a comparison product and is an unstretched film; the same applies below) was measured in accordance with JIS-K7361 using a haze meter NDH-5000 manufactured by Nippon Denshoku Industries Co., Ltd.

[0195] (3-2) Measurement of dielectric breakdown strength and dielectric strength maintenance rate The dielectric breakdown strength at high temperatures of the stretched films obtained in the examples and comparative examples was evaluated as follows. A measuring device was prepared according to JIS C2151:2006, 17.2.2 (plate electrode method). However, as the lower electrode, a conductive rubber (E12S10 manufactured by Seiwa Electric Co., Ltd.) was used instead of the elastic body described in JIS C2151:2006, 17.2.2, and aluminum foil was not wrapped around the electrode.

[0196] The measurement environment was a forced circulation oven set at a temperature of 120°C or 135°C, and the electrodes and films were used after 30 minutes of temperature adjustment in the oven. The voltage was increased at a rate of 100V / sec starting from 0V, and the voltage at which the current value exceeded 5mA was taken as the dielectric breakdown voltage. The dielectric breakdown voltage was measured 20 times, and each dielectric breakdown voltage value V DC Divide by the thickness (μm) of the stretched film, and the average of the 16 points excluding the top 2 and bottom 2 points out of the 20 calculation results is calculated as the dielectric breakdown strength (V DC / μm).

[0197] The dielectric strength retention rate (%) was calculated as the ratio of the dielectric breakdown strength in a 135°C environment to the dielectric breakdown strength in a 120°C environment obtained by the above measurement (dielectric breakdown strength in a 135°C environment / dielectric breakdown strength in a 120°C environment).

[0198] (3-3) Measurement of elongation rate (evaluation of rigidity) The stretched films of the Examples and Comparative Examples, which were sampled in a rectangular shape with a length of 25 mm in the machine direction (MD) and a length of 4 mm in the transverse direction (TD), were set on a quartz tensile probe using a thermo-mechanical measuring device (TMA) TMA / SS6000 manufactured by Seiko Instruments Inc. A static load was applied in the MD direction of the stretched film at a rate of 16.67 mN per 1 μm of thickness depending on the thickness of the stretched film, and the film was heated from 25° C. at a heating rate of 10° C. / min, and the elongation rate (%) from the initial length (25° C.) at a furnace temperature of 130° C. was measured.

[0199] Measurement equipment: Seiko Instruments Inc. TMA / SS6000 type Measurement probe: Quartz tensile probe Measurement mode: F mode (load control mode) Static load: Depends on the thickness of the stretched film, at a ratio of 16.67 mN per 1 μm of thickness Initial chuck distance: 15mm Temperature range: 25℃~170℃ Heating rate: 10℃ / min Data sampling time: 0.5 sec

[0200] (3-4) Evaluation of vapor deposition process passability The stretched film rolls of the Examples and Comparative Examples were used to evaluate the passability through the deposition process by a vacuum deposition method. Using a vacuum deposition device EWE-060 manufactured by ULVAC, Inc., aluminum was deposited on the corona-treated side of the stretched film at a tension of 40 N / m, a deposition speed of 150 m / min, and an electron beam irradiation output of -3.5 KV for adhering the stretched film to the cooling roll that holds the stretched film in close contact during deposition, so that the surface resistivity of the metal film was 20 Ω / □.

[0201] In this case, in addition to both transverse ends of the stretched film, nine 4 mm wide insulating margins (vertical margins) were provided at equal intervals where no metal was laminated. The 11 areas where no metal was laminated (two at both transverse ends and nine vertical margins) tend to be more difficult to peel off from the cooling roll than the areas where metal was laminated.

[0202] The stretched film may break due to the difference in peelability, the effect of heat from the metal during deposition, etc. Under these conditions, deposition was performed on a 5,000 m length, and the deposition process passability was evaluated according to the following criteria. ◯: The stretched film did not break even once (0 times). ×: The stretched film breaks at least once.

[0203] (4) Measurement and evaluation results The results of measurement and evaluation of the physical properties and characteristics of the stretched films of the Examples and Comparative Examples are shown in Table 2.

[0204] From the above evaluation results, it was found that the stretched films (Examples 1 to 10) having an A layer containing 55% by mass or more and 99% by mass or less of a polypropylene-based resin and 1% by mass or more and 45% by mass or less of a polymer having an alicyclic structure in a side chain, with the mass of the A layer being 100%, and in which the A layer is stretched in at least one direction, suppress the decrease in rigidity and the decrease in electrical insulation even in a high-temperature environment exceeding 110°C, and are excellent in their own stretchability and passability through post-processing steps.

[0205] [Table 2]

Claims

1. A stretched film for a film capacitor having at least an A layer, (1) The A layer contains, in 100% by mass, 55% by mass or more and 99% by mass or less of a polypropylene-based resin and 1% by mass or more and 45% by mass or less of a polymer having an alicyclic structure in a side chain, (2) The layer A is stretched in at least one direction, (3) The elongation rate of the stretched film is 0.2% or more and 4.5% or less, (4) The thickness of the stretched film is 10 μm or less. A stretched film characterized by:

2. 2. The stretched film according to claim 1, wherein the A layer contains, based on 100 mass%, 55 mass% to 97 mass% of a polypropylene-based resin and 3 mass% to 45 mass% of a polymer having an alicyclic structure in a side chain.

3. The stretched film according to claim 1 , wherein the polymer has a glass transition temperature of 100° C. or more and 180° C. or less.

4. The stretched film according to claim 1 , wherein the alicyclic structure has a cyclohexane structure.

5. The stretched film according to claim 1 , wherein the stretched film has a total light transmittance of 80% or more.

6. A metal laminated film comprising the stretched film according to any one of claims 1 to 5 and a metal layer laminated on one or both sides of the film.

7. A film capacitor comprising the stretched film according to any one of claims 1 to 5.

8. A film capacitor comprising the metal laminate film according to claim 6.